Atad3a suppresses Pink1-dependent mitophagy to maintain homeostasis of hematopoietic progenitor cells. (January 2018) - Jin, Guoxiang; Xu, Chuan; Zhang, Xian; Long, Jie; Rezaeian, Abdol Hossein; Liu, Chunfang; Furth, Mark; Kridel, Steven; Pasche, Boris; Bian, Xiu-Wu; Lin, Hui-Kuan
Abstract Although deletion of certain autophagy-related genes has been associated with defects in hematopoiesis, it remains unclear whether hyperactivated mitophagy affects the maintenance and differentiation of hematopoietic stem cells (HSCs) and committed progenitor cells. Here we report that targeted deletion of the gene encoding the AAA+-ATPase Atad3a hyperactivated mitophagy in mouse hematopoietic cells. Affected mice showed reduced survival, severely decreased bone-marrow cellularity, erythroid anemia and B cell lymphopenia. Those phenotypes were associated with skewed differentiation of stem and progenitor cells and an enlarged HSC pool. Mechanistically, Atad3a interacted with the mitochondrial channel components Tom40 and Tim23 and served as a bridging factor to facilitate appropriate transportation and processing of the mitophagy protein Pink1. Loss of Atad3a caused accumulation of Pink1 and activated mitophagy. Notably, deletion ofPink1 inAtad3a -deficient mice significantly 'rescued' the mitophagy defect, which resulted in restoration of the progenitor and HSC pools. Our data indicate that Atad3a suppresses Pink1-dependent mitophagy and thereby serves a key role in hematopoietic homeostasis. The survival of hematopoietic stem cells requires tight regulation of mitophagy. Lin and colleagues show that Atad3a regulates mitophagy in these cells by sequestering the mitophagy initiator Pink1 and directing its import via the mitochondrial Tom40–Tim23 complex.